COUMESTROL FEEDING - AN ATTEMPT TO DEVELOP A TOOL FOR STERILIZATION OF MALE STRAY DOGS - KUMAR, R; SHARMA, A K; PANDEY, A K (The Indian Journal of Animal Reproduction, 2022)
Coumestrol dissolved in di-methyl sulfoxide (DMSO) was fed (50 mg, p.o., single dose) to a dog, whereas, the other dog was fed DMSO only. This followed castration of both the dogs on day 30 post-feeding. Microscopic examination revealed normal rete testis, efferent ductules, seminiferous epithelial cycle and spermiogenesis in both the dogs suggesting that coumestrol had no impact. Thus, 50 mg coumestrol as a single per-oral dose cannot be used for the sterilization of male dogs.